2016
DOI: 10.1111/jzs.12156
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the glacial refugia ofErebia euryale(Lepidoptera, Nymphalidae) - insights from mtDNA- and nDNA-based phylogeography in the Western Carpathians

Abstract: The refugial history and postglacial re‐colonization routes of Western Carpathian insects are insufficiently understood. Therefore, we investigated the spatio‐genetic structure (phylogeography) of Western Carpathian populations of Erebia euryale (Esper, 1805) (Lepidoptera, Nymphalidae) and inferred their colonization routes over the postglacial period. Our results provide new insights into the phylogeography and origin of Erebia euryale in the rarely studied region of the Western Carpathian Mountains. Their ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Varga, 2012) for S. aglaja, as observed for some other Lepidoptera species, such as Polyommatus coridon(Kühne et al, 2017), Erebia euryale(Paučulová et al, 2017) and Coenonympha arcania(Cassel- Lundhagen et al, 2020).distances in females and a lifespan twice as long as in males, which would support the hypothesis of sex-biased dispersal as the reason for the observed mitonuclear discordance. Most other explanations…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Varga, 2012) for S. aglaja, as observed for some other Lepidoptera species, such as Polyommatus coridon(Kühne et al, 2017), Erebia euryale(Paučulová et al, 2017) and Coenonympha arcania(Cassel- Lundhagen et al, 2020).distances in females and a lifespan twice as long as in males, which would support the hypothesis of sex-biased dispersal as the reason for the observed mitonuclear discordance. Most other explanations…”
supporting
confidence: 57%
“…Because mtDNA is more vulnerable to selective sweeps, such phenomena can be observed more strongly when sequencing the mtDNA. In contrast to nuclear data attained via ddRADseq, the most distinct lineage formed by Eastern European samples (Ag1, 6 bp from the rest) suggests that some areas in the Carpathians might have constituted an extra‐Mediterranean microrefugium (Schmitt & Varga, 2012) for S. aglaja , as observed for some other Lepidoptera species, such as Polyommatus coridon (Kühne et al, 2017), Erebia euryale (Paučulová et al, 2017) and Coenonympha arcania (Cassel‐Lundhagen et al, 2020). An early split might have happened between this region and the rest of Europe (Schmitt & Varga, 2012), with the Carpathians staying separated for a relatively long time and thus being less affected by gene flow or selective sweeps.…”
Section: Discussionmentioning
confidence: 87%
“…A mtDNA based study (Vila et al 2011) revealed that (i) the populations from the Pyrenees and Cantabria represent a single lineage, and (ii) the ocellaris and isarica samples are phylogenetically closer to syrmia than to each other. Paučulová et al (2017) found two genetic lineages in the Carpathians and the Sudeten Mts, coinciding with the morphologic ssp. euryale and syrmia, and established the border between them.…”
Section: Introductionmentioning
confidence: 72%
“…Additional COI sequences were retrieved from BOLD and GenBank, from localities not represented in our samples. These covered bp 1-658 (Dincă et al 2010), bp 668-1483 (Vila et al 2011) or bp 305-1475 (Paučulová et al 2017) (Table 1, Suppl. material 1: Table S1).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation